2023
DOI: 10.21608/avmj.2022.173957.1100
|View full text |Cite
|
Sign up to set email alerts
|

Semen Quality, Testicular Characteristic, Biochemical Profile and Histopathology of Testes of Goats Under Heat Stress Conditions

Abstract: High temperature during hot summer months is associated with poor animal reproductive performance. The study aimed to explore the seasonal thermal impacts on the bucks fertility. Twenty healthy mature bucks were used in this study. Depending on environmental temperature, bucks were equally divided into two groups: Winter season (n=10) and Summer season (n=10). Scrotal width, circumstances, length and diameter of right and left testicles, as well as length of right and left testicles were evaluated. From each g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Testicular length, testicular diameter, and scrotal thickness were determined with a metal caliper precision of 0.01 mm [11]. The scrotal circumference, scrotum width, and scrotum length were measured by a tape measure [11,12].…”
Section: Clinical Examination Sample Collection and Animal Handlingmentioning
confidence: 99%
See 1 more Smart Citation
“…Testicular length, testicular diameter, and scrotal thickness were determined with a metal caliper precision of 0.01 mm [11]. The scrotal circumference, scrotum width, and scrotum length were measured by a tape measure [11,12].…”
Section: Clinical Examination Sample Collection and Animal Handlingmentioning
confidence: 99%
“…About glucose (Cod: GL13 20, Biodiagnostic, Egypt) using a wavelength 510 nm (490-530), total protein (Cod; TP20 20, Biodiagnostic, Egypt) using a wavelength 550 nm (520-570), cholesterol (CHOD-PAP, Cod; 230001, Spectrum ® , Egypt) using wavelength 546 nm, albumin (Cod; ALB100250, BIO-TEC Egypt) using a wavelength 580-630 nm, and triglyceride (Medium-Chain Triglycerides, Cod; M4200, Spectrum ® , Egypt) using a wavelength 500-550 nm. The biochemical were measured by spectrophotometer (UV/VIS spectrometer-T80) [12].…”
Section: Clinical Examination Sample Collection and Animal Handlingmentioning
confidence: 99%
“…Further research is needed to reveal this issue. However, what certain was that increasing environmental temperature had been proven to reduce semen quality in experimental animals (Octaviani et al, 2021;Panggalih et al, 2021;Prastyaningtyas et al, 2021), as well as in livestock (Llamas-Luceño et al, 2020;Gloria et al, 2021;Sun et al, 2022;Mohamed et al, 2023;Moula et al, 2024). Therefore, efforts need to be made to maintain male fertility by controlling the temperature of the cage air and environment and providing antioxidants as additional feed (Pham and Schultz, 2021).…”
Section: ____________________________________________________________...mentioning
confidence: 99%
“…However, environmental temperatures that were higher than normal and persisted for a long time could disrupt male fertility. Several publications reported that increasing environmental temperature could reduce the semen quality of Mediterranean buffalo (Sun et al, 2022), Belgian Blue bulls (Gloria et al, 2021), Holstein Friesian bulls (Llamas-Luceño et al, 2020), ram (Moula et al, 2024), and buck (Mohamed et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation